Community Information Concepts - Vishwa Mohan, V.; Raju, A.A.N. (DESIDOC Journal of Library & Information Technology, 2003)
This article discusses the definitions and concepts of community information (CI) and community information serivices (CISs), given by several authors. It traces the history and details the components of CI and CISs. http://dx.doi.org/10.14429/dbit.19.1.3454